Santé mentale des jeunes des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : l’état des lieux - Beaton, Ann M.; Benoit, Monique; Mulatris, Paulin; Dupuis, Jérémie B. (/Youth Mental Health in Official Language Minority Communities (OLMCs) in Canada: Situation Analysis Minorités linguistiques et société, 2018)

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H., Gilbert, A. et Dubois, L. (2009). La santé en situation linguistique minoritaire. Politiques de Santé, 4(4), 36-42. https://www.ncbi.nlm.nih.gov/pmc/Article de revue s/PMC2700700/pdf/policy-04-036.pdf fs-code-orig: Bouchard-2009a

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.
fs-ref-orig: Leis, A. et Bouchard,

Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. - Official Language Community Development Bureau (Health Canada, 2007)
fs-ref-orig: Official Language Community Development Bureau. (2007). Contribution Program to improve access to health services for Official Language Minority Communities. Formative evaluation. Health Canada. fs-code-orig: Official Language Community Development Bureau-2007

Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? - Puchala, Chassidy; Leis, Anne; Lim, Hyun; Tempier, Raymond (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
fs-ref-orig: Puchala, C., Leis, A., Lim, H., & Tempier, R. (2013). Official language minority communities in Canada: Is linguistic minority status a determinant of mental health? Canadian Journal of Public Health, 104(1), 5‑11. https://www.ncbi.nlm.nih.gov/pmc/Articles/PMC6973939/pdf/41997_2013_Article_1040605.pdf fs-code-orig: Puchala-2013

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Comparing the rates of mental disorders among different linguistic groups in a representative Canadian population - Vasiliadis, Helen-Maria; Lepnurm, Marje; Tempier, Raymond; Kovess-Masfety, Viviane (Social psychiatry and psychiatric epidemiology, 2012)
Purpose We aimed to determine whether linguistic group influences reported prevalence rates for a number of common mental disorders. Methods Secondary data analyses of the Canadian Community Health Survey cycle 1.2 (CCHS 1.2) were carried out on representative bilingual French and English, monolingual French and English and other language groups in Canada. Past year prevalence of major depression, anxiety disorders (agoraphobia, social phobia, panic disorder) and alcohol abuse/dependence were ascertained using versions of the World Mental Health Composite International Diagnostic Interview (WMH-CIDI) questionnaire. Multivariate data analyses were used to model past year presence of a mental disorder as a function of linguistic group, defined as languages can converse in, and adjusting for socioeconomic, demographic and cultural factors. Results Overall, past year rates for the presence of a common mental disorder were 10.7% (9.7–11.7%) for the bilingual English; 9.0% (8.1–9.9%) for the bilingual French; 10.2% (9.8–10.6) for the monolingual English; 8.5% (7.7–9.3%) for the monolingual French; and 8.3% (6.1–10.4%) for the other language group. After adjusting for a number of socio-demographic, economic and cultural factors, the multivariate analyses showed that the linguistic groups were equally likely to report the presence of a past year common mental disorder. This was also true for comparisons between the bilingual participants responding in French and English. Conclusions The differences observed in the reported crude rates for the presence of mental disorders across the different linguistic groups in Canada were explained by socio-demographic, economic, and factors such as immigration, spoke a third language and province of residence, and not explained by language of interview.